Bone marrow mesenchymal stem cells regulate TGF‐β to adjust neuroinflammation in postoperative central inflammatory mice - Sun, Zhen‐Zhen; Li, Yun‐Feng; Xv, Zhi‐Peng; Zhang, You‐Zhi; Mi, Wei‐Dong (Journal of cellular biochemistry, 2020)
Background Postoperative cognitive dysfunction (POCD) is one of the common postoperative complications, which is more common in aged patients. POCD mainly manifests as cognitive function changes after surgery, such as memory decline and inattention. In some severe cases, patients may suffer from personality changes and (or) social behavior decline. The aim of the current study is to confirm the effect and elucidate the mechanism of bone marrow mesenchymal stem cells (BMSCs) in postoperative central inflammatory mice. Methods Mice were randomly assigned to four groups: sham, sham+BMSCs, model, and BMSCs group. In the model group, mice were intraperitoneally injected 8 mg/kg per day lipopolysaccharide for 5 days. In sham+BMSCs and BMSCs group, BMSCs (1 × 10 7) in 100 µL saline were injected into sham mice and model mice, respectively. Results In the model group, transforming growth factor β (TGF‐β) protein expression was significantly increased, compared with that in the sham group. BMSCs were treated into postoperative central inflammatory mice, which resulted in a decreased of TGF‐β protein expression. TGF‐β and smad2 protein expression were suppressed, and apoptosis rate and inflammation were inhibited in coculture with BMSCs. The suppression of TGF‐β inhibited the effects of BMSCs on apoptosis rate and inflammation in postoperative central inflammatory through a smad2 signaling pathway. The promotion of TGF‐β reduced the effects of BMSCs on apoptosis rate and inflammation in postoperative central inflammatory through a smad2 signaling pathway. Conclusion The present study demonstrates that BMSCs regulates TGF‐β to adjust neuroinflammation in postoperative central inflammatory mice.